Antioxidant properties of Melissa officinalis L. callus cultures - Topdemir, Aykut; Gür, Nazmi; Demir, Zümre (Muhammet DOĞAN, 2018)
Melissa officinalis L. is a Mediterranean plant from the family of the Labitae, and has lemon fragrance. Melissa is a perennial herbaceous plant that forms the plant size between 60-100 cm. It is a known and used plant for a long time, because of its pleasant smell. Because it is effective in beekeeping, this plant is called as the swarm plant. It is a medicinal and aromatic plant, since it contains essential oils containing citral, stranellal, linalool and pinemia and flavonoid and resin. The antioxidant activity of the in vitro produced calli was determined in this study, which was also determined by previous studies. Melissa officinalis L. nodals were used as an explant source. Nodules were promoted with different plant growth regulator combinations for callus formation in Murashige Skoog medium. The antioxidant activity of the resulting callus was determined by the ABTS method and the results were given as "TEAC (tropoxyl equivalent antioxidant capacity) equivalent". The highest antioxidant capacity (0.365 mmol / L) was seen in 1.5 mg / L 2,4-D + 1 mg / L PIC + 0.5 mg / L KIN-induced callus. The lowest value (0.191 mmol / L) was obtained from calli promoted with 1.5 mg / L 2,4-D + 0.5 mg / L BAP.

Melissa officinalis L., Labitae familyasından, Akdeniz bitkisi olup  limon kokuludur. Melisa 60-100 cm arasında bitki boyu oluşturan çok yıllık otsu bir bitkidir. Hoş kokusu nedeniyle uzun zamandır bilinen ve kullanılan bir bitkidir. Arıcılıkta oğul ekmede etkili olduğu için, halk arasında bu bitkiye oğul otu da denilmektedir. Sitral,stranellal,linalol ve pinemi içeren uçucu yağlar ile flavonoid ve reçine içerdiğinden dolayı tıbbi ve aromatik bir bitkidir. Çalışmamızda antoksidan özelliği olduğu da daha önce yapılan çalışmalarla belirlenmiş olan bu bitkiden, in vitro olarak üretilen kallusların antioksidan aktivitesi belirlenmiştir. Explant kaynağı olarak Melissa officinalis L. nodları kullanılmıştır. Nodlar Murashige Skoog besiyerinde kallus oluşumu için farklı bitki büyüme düzenleyici kombinasyonları ile teşvik edilmiştir. Sonuçta oluşan kallusların antioksidan aktivitesi ABTS yöntemi ile belirlenmiş ve sonuçlar “TEAC (troloks eşdeğer antioksidan kapasite) eşdeğeri” olarak verilmiştir. En yüksek antioksidan kapasite (0.365 mmol/L), 1.5 mg/L 2,4-D + 1 mg/L PİC + 0.5 mg/L KİN ile indüklenmiş kalluslarda görülmüştür. En düşük değer ise (0.191 mmol/L), 1.5 mg/L 2,4-D + 0.5 mg/L BAP ile teşvik edilmiş kalluslardan elde edilmiştir.
Melissa officinalis L. kallus kültürlerinin antoksidan özellikleri